2012
DOI: 10.1259/bjr/57130600
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of incident hip fracture by femoral neck bone mineral density and neck–shaft angle: a 5-year longitudinal study in post-menopausal females

Abstract: Objective: To compare hip fracture incidence in post-menopausal females who were differently stratified for the fracture risk according to bone mineral density and proximal femur geometry. Methods: In a 5 year follow-up study, the hip fracture incidence in 729 postmenopausal females (45 of whom suffered from incident hip fracture) was assessed and compared. Forward logistic regression was used to select independent predictors of hip fracture risk, including age, age at menopause, height, weight, femoral neck b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…The relationship of hip fractures with the hip axis length and neck-shaft angle measured by DXA scan has been investigated for years. A longer hip axis length9,18 and wider neck-shaft angle33 were found to be associated with hip fracture independently of BMD in postmenopausal women. Hip axis length and neck-shaft angle were comparable between patients with type 1 diabetes and controls in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…The relationship of hip fractures with the hip axis length and neck-shaft angle measured by DXA scan has been investigated for years. A longer hip axis length9,18 and wider neck-shaft angle33 were found to be associated with hip fracture independently of BMD in postmenopausal women. Hip axis length and neck-shaft angle were comparable between patients with type 1 diabetes and controls in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…The femoral neck shaft angle (NSA) has been reported to be an independent predictor of hip fracture risk (Alonso et al, ; Gnudi et al, ). In a United Kingdom (UK) population (Tuck et al, ), the NSA in the female was significantly smaller than in the male, which is inconsistent with those measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…All 3 of the longitudinal studies were BMD adjusted. The 2 studies with a follow-up of 5e10 yr found a small but significant association with an OR or HR per SD increase ranging from 1.11 to 1.15 (36,40). Although the 3rd study by Faulkner et al with 64 hip fractures ˃1.6 yr found no significant association: OR of 1.0 (95% CI 0.7e1.5) for FN fractures and 1.4 (95% CI 0.9e2.2) for trochanteric fractures, this was an early report of this cohort in 1993 (18).…”
Section: Neck-shaft Anglementioning
confidence: 99%